Translation and/as simulation: first attempts at imitating James Joyce’s Ulysses in Hong Kong, 1960-1963 - Tak-hung Chan, Leo (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Imitations of texts of foreign origin, as a form of cross-cultural rewriting, are of considerable interest to literary comparatists, though much of this interest has been targeted at the transference of thematic material. The concept of influence becomes incurably vague in many accounts of Chinese imitations of Western literature, for instance, precisely because the ‘textual’ links are neglected. The author believes that translation studies can help throw some light on what influence is all about, in ways that comparative literary studies has not. The present article focuses specifically on three Chinese imitations of Joyce ’s Ulyssesfrom the early 1960s, all published in Hong Kong. The styles and strategies of these imitations are contrasted with those of one translation of the “Hades” episode from 1960. In the conclu-sion, an attempt is made to address the different conceptualizations of imitation in China and the West, and to justify the inclusion of imitations as a viable object of investigation in translation studies.